Anomaly driven signatures of new invisible physics at the Large Hadron Collider - Antoniadis, Ignatios; Boyarsky, Alexey; Espahbodi, Sam; Ruchayskiy, Oleg; Wells, James D. (Nuclear physics. B, 2010)
Many extensions of the Standard Model (SM) predict new neutral vector bosons at energies accessible by the Large Hadron Collider (LHC). We study an extension of the SM with new chiral fermions subject to non-trivial anomaly cancellations. If the new fermions have SM charges, but are too heavy to be created at LHC, and the SM fermions are not charged under the extra gauge field, one would expect that this new sector remains completely invisible at LHC. We show, however, that a non-trivial anomaly cancellation between the new heavy fermions may give rise to observable effects in the gauge boson sector that can be seen at the LHC and distinguished from backgrounds.